2012
DOI: 10.1590/s0103-64402012000500014
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms of black tooth stains: PCR analysis reveals presence of Streptococcus mutans

Abstract: This study investigated the presence of the black-pigmented bacteria Prevotella nigrescens and Prevotella intermedia, the non-black-pigmented bacteria Actinomyces spp and particularly the cariogenic pathogen Streptococcus mutans in the dental biofilms of patients with or without black extrinsic tooth stains, using the multiplex polymerase chain reaction (PCR) technique. Analysis of the dental biofilms of patients with (n=26) or without (n=26) black tooth stains was performed using duplex PCR for the 16S riboso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 23 publications
4
19
0
6
Order By: Relevance
“…These findings are in contrast with other studies, in which Actinomyces spp. were the most prevalent species [28]. The most recent PCR study confirmed that Actinomyces naeslundii is more prevalent in BS patients.…”
Section: Microbiology Of Black Stainmentioning
confidence: 99%
“…These findings are in contrast with other studies, in which Actinomyces spp. were the most prevalent species [28]. The most recent PCR study confirmed that Actinomyces naeslundii is more prevalent in BS patients.…”
Section: Microbiology Of Black Stainmentioning
confidence: 99%
“…Several studies showed that there is a positive correlation between high surface roughness and discoloration of denture resins, which is explained by the large surface with various predilection sites for agglomerating colorants [23,24|. Combined with bacterial adhesion and transformation of biofilm this cannot only result in development of caries and periodontal disease but also in further discoloration caused by metabolic products of bacteria [25,26]. Therefore, effective cleaning methods are required.…”
Section: Introductionmentioning
confidence: 99%
“…Garan et al 43 found that salivary pH was not signifi cantly different between the groups with and without black stains. Costa et al 44 and Li et al 40 report on a similar prevalence of S. mutans in dental biofi lms of patients with and without black stain. Th e presence of black stain has been reported to be associated with a low frequency of caries, but the reasons are still unknown 23 .…”
Section: Discussionmentioning
confidence: 80%